2011
DOI: 10.1103/physrevlett.107.225504
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Structure, Interfacial Cohesion, Adsorbed Layers, and Thermodynamics in Dense Polymer-Nanoparticle Mixtures

Abstract: We establish the existence and size of adsorbed polymer layers in miscible dense nanocomposites and their consequences on microstructure and the bulk modulus. Using contrast-matching small-angle neutron scattering to characterize all partial collective structure factors of polymers, particles, and their interface, we demonstrate qualitative failure of the random phase approximation, accuracy of the polymer reference site interaction model theory, ability to deduce the adsorbed polymer layer thickness, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 23 publications
8
95
1
Order By: Relevance
“…This increase is consistent with the results from Roland and coworkers 18 for a PVAc nanocomposite. The result is also consistent with the prediction by Schweizer and coworkers, 12 where they reported that the bulk modulus can either increase or decrease depending on the interaction of the nanoparticle with the polymer, with increases predicted for weaker interfacial attraction strength, which seems to be the case for our nanocomposite sample. In fact, in another report by Schweizer and coworkers, 53 they specifically show that in aggregated fluid systems, the bulk modulus is predicted to be higher than the hard sphere system at low volume fraction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This increase is consistent with the results from Roland and coworkers 18 for a PVAc nanocomposite. The result is also consistent with the prediction by Schweizer and coworkers, 12 where they reported that the bulk modulus can either increase or decrease depending on the interaction of the nanoparticle with the polymer, with increases predicted for weaker interfacial attraction strength, which seems to be the case for our nanocomposite sample. In fact, in another report by Schweizer and coworkers, 53 they specifically show that in aggregated fluid systems, the bulk modulus is predicted to be higher than the hard sphere system at low volume fraction.…”
Section: Discussionsupporting
confidence: 93%
“…[9][10][11][12] The results show that the pressure-dependent liquid bulk modulus increases 14% for the nanocomposite compared to the neat unfilled system. This increase is consistent with the results from Roland and coworkers 18 for a PVAc nanocomposite.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We particularly highlight the work by Zukoski and Schweizer which shows excellent agreement between theory and experimentally determined structure factors in the case of polymer solutions containing NPs. 171 Computer simulations with explicit representation of NP and polymer degrees of freedom (in contrast to the hybrid approach discussed above) have also been used. For instance, de Pablo et al have developed a number of MC techniques to study the structure and properties of polymer nanoparticle mixtures.…”
Section: Phase Behavior In Polymer-nanoparticle Mixturesmentioning
confidence: 99%
“…[4][5][6][7] It is now understood that the motion of NPs smaller than the entanglement mesh size is dictated by local Rouse dynamics of the chains while larger particles are significantly slowed down by the entanglements resulting in a sub-diffusive motion [8,9]. The NP effect on the dynamics of the polymer in the nanocomposites has also been the focus of many experimental and theoretical works mostly considering large NPs [10][11][12][13][14][15][16][17]. A recent molecular dynamics simulation [17] and primitive path analysis [16] emphasizes the particle size effects on the local segmental dynamics in attractive and repulsive systems.…”
mentioning
confidence: 99%